Prescription of therapeutic exercise in migraine, an evidence-based clinical practice guideline - Roy La Touche; José Fierro-Marrero; Irene Sánchez-Ruíz; Borja Rodríguez de Rivera-Romero; Carlos Donato Cabrera-López; Sergio Lerma-Lara; Néstor Requejo-Salinas; Francisco de Asís-Fernández; Ignacio Elizagaray-García; Josué Fernández-Carnero; Luís Matesanz-García; Joaquín Pardo-Montero; et al. (The Journal of Headache and Pain, 2023)
Abstract The main objective of this clinical practice guideline is to provide a series of recommendations for healthcare and exercise professionals, such as neurologists, physical therapists, and exercise physiologists, regarding exercise prescription for patients with migraine. This guideline was developed following the methodology and procedures recommended in the Appraisal of Guidelines for Research and Evaluation (AGREE). The quality of evidence and strength of recommendations were evaluated with the Scottish Intercollegiate Guidelines Network (SIGN). A systematic literature review was performed and an established appraisal process was employed to rate the quality of relevant scientific research (Grading of Recommendations Assessment, Development, and Evaluation methodology). The evaluation of the current evidence, the elaboration of the grades of recommendation, and their validation show a B grade of recommendation for aerobic exercise, moderate-continuous aerobic exercise, yoga, and exercise and lifestyle recommendations for the improvement of symptoms, disability, and quality of life in patients with migraine. Relaxation techniques, high-intensity interval training, low-intensity continuous aerobic exercise, exercise and relaxation techniques, Tai Chi, and resistance exercise obtained a C grade of recommendation for the improvement of migraine symptoms and disability.